Research progress on the effect of gut and tumor microbiota on antitumor efficacy and adverse effects of chemotherapy drugs - Yin, Beibei; Wang, Xuan; Yuan, Fang; Li, Yan; Lu, Ping (Frontiers in Microbiology, 2022)
Chemotherapy is one of the most effective methods of systemic cancer treatment. Chemotherapy drugs are delivered through the blood circulation system, and they can act at all stages of the cell cycle, and can target DNA, topoisomerase, or tubulin to prevent the growth and proliferation of cancer cells. However, due to the lack of specific targets for chemotherapeutic agents, there are still unavoidable complications of cytotoxic effects. The effect of the microbiome on human health is clear. There is growing evidence of the potential relationship between the microbiome and the efficacy of cancer therapy. Gut microbiota can regulate the metabolism of drugs in several ways. The presence of bacteria in the tumor environment can also affect the response to cancer therapy by altering the chemical structure of chemotherapeutic agents and affecting their activity and local concentration. However, the underlying mechanisms by which the gut and tumor microbiota affect cancer therapeutic response are unclear. This review provides an overview of the effects of gut and tumor microbiota on the efficacy and adverse effects of chemotherapy in cancer patients, thus facilitating personalized treatment strategies for cancer patients.